2010
DOI: 10.1016/j.bpj.2010.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Conditions Affect the Kinetics of Nucleation of Amyloid Fibrils and Determine Their Morphology

Abstract: To understand and tackle amyloid-related diseases, it is crucial to investigate the factors that modulate amyloid formation of proteins. Our previous studies proved that the N47A mutant of the α-spectrin SH3 (Spc-SH3) domain forms amyloid fibrils quickly under mildly acidic conditions. Here, we analyze how experimental conditions influence the kinetics of assembly and the final morphology of the fibrils. Early formation of curly fibrils occurs after a considerable conformational change of the protein and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 47 publications
5
108
1
Order By: Relevance
“…We found that the rate of nucleation is strongly affected by sequence mutations and experimental conditions, in particular temperature, pH and the concentrations of protein and salt, resulting in considerable changes in the governing kinetics and also in the morphological properties of the finally assembled fibrils [23]. For instance, at low salt concentration the aggregation shows a considerable lag phase, as usually observed for nucleation-dependent polymerization, resulting in well-ordered straight and twisted amyloid fibrils.…”
Section: Introductionmentioning
confidence: 71%
“…We found that the rate of nucleation is strongly affected by sequence mutations and experimental conditions, in particular temperature, pH and the concentrations of protein and salt, resulting in considerable changes in the governing kinetics and also in the morphological properties of the finally assembled fibrils [23]. For instance, at low salt concentration the aggregation shows a considerable lag phase, as usually observed for nucleation-dependent polymerization, resulting in well-ordered straight and twisted amyloid fibrils.…”
Section: Introductionmentioning
confidence: 71%
“…The ability of the N47A mutant to form amyloid is, however, extremely sensitive to the conditions of the medium (e.g., at pH ≥ 3.8, the formation of amyloid fibrils is no longer observed), including temperature and protein concentration. 18,46 On the other hand, the formation of amyloid by the triple mutant D48G(2Y) occurs much faster and more efficiently (i.e., with a higher percentage of aggregated protein in the same amount of time) than in the N47A. In the triple mutant's case, the process is also considerably more robust with regard to environmental changes, actually occurring over a wider range of pH.…”
Section: Protein Studiedmentioning
confidence: 95%
“…Malfunction of the SH3 domain has a significant impact on such important processes as p53-mediated apoptosis and DNA repair (Jiang et al 2001), adhesion-dependent regulation by tyrosine phosphorylation (Moore and Winder 2010), stimulation of mesenchymal stem cell migration, which is important for hypoxic solid tumor development (ProulxBonneau et al 2011), osteoblast maturation and consequently bone formation (Levaot et al 2011), the assembly of amyloid fibrils and determination of their morphology (Morel et al 2010), processes associated with a number of neurodegenerative diseases, such as Alzeimer's (Morel et al 2010), tyrosine phosphatase signaling that affects SH3 binding in patients with rheumatoid arthritis (Bilwes et al 1999), bacteria adhering to host cells (Queval et al 2011) and contraction-induced injuries (Banks et al 2010). Mutations in the SH3 domain of unconventional myosin VIIa have recently been shown to cause deafness in humans, with one mutation, A1628S, located directly in its SH3 domain (Wu et al 2011).…”
Section: Regulationmentioning
confidence: 99%